THE RATIONALE OF LAW. THE ROLE AND IMPORTANCE OF THE LOGICAL METHOD OF INTERPRETATION OF LEGAL NORMS - Mihai BĂDESCU (Challenges of the Knowledge Society)
The interpretation of law was and remains an indispensable postulation, inherent and the most significant in the application of the law. Through interpretation the aim is to clarify the obscure text, to rectify the imperfection of the text of the legal norm, to remedy its shortcomings, and in consequence, to specify the exact meaning of the legal norm. Interpretation concerns itself with emphasizing the authentic meaning of the normative texts, finding the spirit of the lawmaker-author, the authentic legal sense of the actions that occurred, of the conduct of the perpetrator, and the significant legal connection of these meanings. The necessity of interpreting legal norms is justified by several considerations, out of which the most important remains the one regarding the act that the lawmaker cannot and need not provide everything in the normative text. The unity between the spirit and the letter of the law, the continuity of interpretation, the useful effect of the legal norm are just a few of the principles that need to be taken into account in interpretation. Be it official (obligatory), or unofficial (doctrinary), interpretation remains an extremely important stage in the application of the law: the literature of specialty consecrates five important methods of interpretation (grammatical, historical, systematical, teleological, and logical). The latter method allows for the formulation by the interpreter of certain rational assessments, done through operations of generalization, of logical analysis of the text, of analogy, through applying formal logic. The present study will mainly deal with this method, analyzing the main logical arguments used in interpretation.